Good Laboratory Practice in Terms of Sample Logistics (Journal of Universal Excellence, 2026)
Research Question (RQ): What is the impact of personnel, information systems and identification on sample logistics from a good laboratory practice perspective?Purpose: To investigate the relationship between personnel, information systems and specimen identification on good laboratory practice in specimen logistics, with the aim of identifying whether any of the three contents is more critical than the other two.Method: We used a qualitative method for the research, where we reviewed and analyzed the literature and information, as well as the example of a selected laboratory in the southeastern region in Slovenia.Results: The results showed that good training and competence of staff is essential for good laboratory practice in sample logistics. The process is supported by an efficient laboratory information system that reduces the risk of errors in the sample traceability process. The key is the clear and unambiguous identification of the samples at the beginning of the process and the traceability of the latter until the end, until the report or conclusion is issued.Organization: The research can be an example of good practice for similar organizations, laboratories testing environmental, human and other samples.Society: On the basis of research, residents of the Republic of Slovenia get an insight into logistics or sample handling and confidence in the traceability and correct identification of samples.Originality: The research is useful for the purpose of the learning process at one of the faculties of the southeastern region in Slovenia.Limitations/Future Research: Only part of the logistics process in the laboratory is included in the research and it only summarizes the literature analysis and one selected case. In the future, it would make sense to expand the research to the area of overall logistics in laboratory activities and review processes in several laboratories.
Keywords: laboratory; logistics; sample; identification; laboratory information system; traceability; digitization